One-month old foreign body in esophagus - Coello Casariego, Guadalupe (2008)
The majority of foreign bodies found in the oesophagus seen atthe emergency department are usually promptly diagnosed and removed endoscopically without complications. ln some cases rarebut severe complications can arise.Take the case of a patient who visited the doctor with disphagiaafter swallowing a watch the previ ous month. The endoscopic extraction failed anda surgical approach was required. Later a serious pneumomediastnum was diagnosed and treated with surgery. A review has been made about the management of foreign bodies in the oesophagus and their complications.